Tailoring Mechanical Properties of Mg–Al–Zn–Sn–Mn Alloy by Multipass Equal Channel Angular Pressing. Issue 1 (6th October 2020) - Zha, Min; Wang, Chun-Xue; Jin, Zhong-Zheng; Jia, Hai-Long; Xu, Hong; Zhang, Ping-Yu; Huang, Yu; Ma, Ping-Kui; Wang, Hui-Yuan
Abstract : Herein, the influence of equal channel angular pressing (ECAP) routes, i.e., A and Bc, on the microstructure and texture evolution of a Mg–3.7Al–0.7Zn–0.8Sn–0.4Mn (wt%) alloy is investigated by scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), and X‐ray diffraction (XRD). It is found that with increasing the number of ECAP passes, the area fraction of the dynamically precipitated secondary‐phase particles increases, whereas particle size becomes larger. After four and six passes of ECAP via route A, shear deformation induced by ECAP promotes the incline of c ‐axes toward extrusion direction (ED). The optimum room temperature (RT) mechanical properties (yield strength of ≈225 MPa, ultimate tensile strength of ≈312 MPa, and elongation to fracture of ≈31.9%) are obtained after four passes of ECAP at 200 °C via route A. The improved strength results from fine dynamic recrystallization (DRX)/ed grains, nanoscale secondary‐phase particles, and basal texture. Herein, it is indicated that Mg–Al–Zn–Sn alloys have great potential as low‐cost high‐strength‐ductility wrought Mg alloys. Abstract : The mechanical properties of Mg–3.7Al–0.7Zn–0.8Sn–0.4Mn (wt%) alloy are optimized by equal channel angular pressing (ECAP) at 200 °C via route A and Bc. The improved strength results from fine dynamic recrystallized (DRXed) grains, nanoscale particles, and basal textures. Herein, Mg–Al–Zn–Sn alloys show great potential as low‐cost high performance wrought Mg alloys.